1989
DOI: 10.1007/bf00247900
|View full text |Cite
|
Sign up to set email alerts
|

Sensory components facilitating jaw-closing muscle activities in the rabbit

Abstract: The role of oral and facial sensory receptors in the control of masticatory muscle activities was assessed from the effect of acute deafferentiation on cortically induced rhythmic jaw movements (CRJMs) in anesthetized rabbits. When a thin polyurethane-foam strip (1.5, 2.5 or 3.5 mm thick) was placed between opposing molars during CRJMs, masseteric activities were facilitated in association with an increase in the medial excursion of the mandible during the power phase. The effects varied with the pattern of CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(110 citation statements)
references
References 56 publications
6
103
0
Order By: Relevance
“…Several studies have shown that increases in food 'hardness' are associated with increases in EMG burst duration (Hidaka et al, 1997;Lavigne et al, 1987;Liu et al, 1993;Lund et al, 1998;Morimoto et al, 1989). On the basis of these EMG data, it might seem reasonable to hypothesize that variation in bite force magnitudes in mammals is significantly correlated with variation in the duration of force generation.…”
Section: Time-modulation Of Bite Forcementioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have shown that increases in food 'hardness' are associated with increases in EMG burst duration (Hidaka et al, 1997;Lavigne et al, 1987;Liu et al, 1993;Lund et al, 1998;Morimoto et al, 1989). On the basis of these EMG data, it might seem reasonable to hypothesize that variation in bite force magnitudes in mammals is significantly correlated with variation in the duration of force generation.…”
Section: Time-modulation Of Bite Forcementioning
confidence: 97%
“…Rate modulation rather than time modulation may allow rhythmic mastication to proceed at a relatively constant frequency, simplifying motor control computation. Masticatory bone strain and bite force modulation 1989;Nakajima et al, 2001). These studies reveal that descending control and afferent information from muscle spindles, Golgi tendon organs, and stretch receptors in the periodontal and 'periarticular' ligaments modulate the motor program and temporal and spatial patterns of jaw movement (Sessle, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is evidence that Mes V neurons form coupled networks among themselves via electrical and excitatory recurrent connections (Baker and Llinas, 1971;Luo and Dessem, 1996). Although they are not directly responsible for setting the oral-motor rhythm during mastication or sucking, they are important for production of appropriate jaw movements (Miles, 1979;Morimoto et al, 1989) and could participate as interneurons because of their central brainstem location and synaptic connectivity (Kolta et al, 1995). As such, they are active during fictive mastication and local stimulation of nearby interneurons produces synaptic potentials, subthreshold oscillations, and spike activity in some Mes V neurons (Verdier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-talk can be minimized by standardizing the experimental conditions. Moreover, double deferential techniques can also assist in eliminating cross-talk [37][38][39][40][41][42][43] . This is the prime cause of criticism in telemetry sEMG recording where cross-talk and noise can compromise the results 44 .…”
Section: Limitations and Methodological Issuesmentioning
confidence: 99%